2004
DOI: 10.1023/b:jacp.0000037778.61929.1b
|View full text |Cite
|
Sign up to set email alerts
|

Time Perception: Does It Distinguish ADHD and RD Children in a Clinical Sample?

Abstract: This study used a double-dissociation design to evaluate whether children with ADHD demonstrated specific deficits relative to children with Reading Disorders. Recent theory suggests that ADHD children have deficits in time perception and working memory, whereas RD children have deficits in phonological decoding. The performance of 113 clinic-referred children aged 6-11 was examined using measures of working memory, phonological processing, and time perception. Respondents completed two time production tasks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 56 publications
3
29
1
Order By: Relevance
“…Thus, the results of this study are in line with studies in which no connection between RAN and attention was found when reading was controlled (Ackerman & Dykman, 1993;; see also Boada et al, 2012 for review). The results of this study also confirmed the findings of previous studies where no connection between PA and attention was found McGee et al, 2004;Purvis & Tannock, 2000, Willcutt et al, 2001.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the results of this study are in line with studies in which no connection between RAN and attention was found when reading was controlled (Ackerman & Dykman, 1993;; see also Boada et al, 2012 for review). The results of this study also confirmed the findings of previous studies where no connection between PA and attention was found McGee et al, 2004;Purvis & Tannock, 2000, Willcutt et al, 2001.…”
Section: Discussionsupporting
confidence: 92%
“…In regard to attention deficit, phonological skills and AD seem not to be related McGee, Brodeur, Symons, Andrade, & Fahie, 2004;Purvis & Tannock, 2000;Willcutt et al, 2001). Instead, a link between naming speed deficit and attention deficit has been suggested (Tannock, Martinussen, & Frijters, 2000), especially for children with AD without impulsivity and hyperactivity (Arnett et al, 2012;.…”
Section: Ddh and Comorbid Problems With Rds: Math Disabilities And Atmentioning
confidence: 99%
“…Nevertheless, there are reports of executive functioning deficits that occur in children with RD only (Närhi & Ahonen, 1995;Willcutt et al, 2005). The role of timing and naming deficits is unclear in the comorbidity of ADHD and RD, and requires further study (McGee et al, 2004;Rucklidge & Tannock, 2002). Furthermore, phonological deficits do not seem to occur in those with ADHD only and thus…”
Section: Cognitive Subtype Hypothesismentioning
confidence: 99%
“…The majority of the findings show that, as occurs in the pure RD group, the ADHD+RD group presents phonological awareness impairments (McGee et al, 2004;Willcutt et al, 2001;Willcutt, Pennington, Olson et al 2005), makes more mistakes, and is slower than controls and pure ADHD on performing all types of phonological processing tasks, such as word and pseudoword reading, phonological suppression, segmentation, phonological synthesis or spelling (McGee et al, 2004;Purvis & Tannock, 2000;Tiffin-Richards et al, 2008;Van de Voorde et al, 2010). Similar deficits seem to occur in adulthood (Laasonen, Lehtinen, Leppämäki, Tani & Hokkanen, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…The idea that ADHD and RD are linked with two opposite patterns of impairments in different processes has also been supported by McGee, Brodeur, Symons, Andrade and Fahie (2004). These authors evaluated phonological awareness, together with time perception and attention, in a sample composed of 4 groups of children (ADHD, RD, ADHD+RD and controls).…”
Section: Adhd and Rd Double Dissociation Studiesmentioning
confidence: 97%